Exploration of Nematophagous Fungi from Coffee Rhizosphere Soil and their Potential as Biological Control Agents against Root-lesion and Root-knot Nematodes - Indarti, Siwi; Aldina, Rinda Fajrin; Widianto, Donny; Prijambada, Irfan Dwidya; Maharani, Rina; Kurniasari, Irianti; Waele, Dirk De (Universitas Gadjah Mada, 2025)
Root-lesion and root-knot nematodes are amongst the most important pathogens of coffee and can cause substantial yield losses and quality reductions. Environmental and health concerns concerning the use of chemical pesticides have increased the need for alternative management strategies against plant-parasitic nematodes. The aim of our study was to isolate and identify nematophagous fungi from nematode-infested coffee production areas and evaluate their potential as biocontrol agents. Our study was carried out in two stages: 1) fungi isolation and evaluation of their ability to affect eggs or vermiform developmental stages of root-lesion and root-knot nematodes; 2) identification of fungal isolates to species level. Eleven fungal isolates were able to affect either the nematode eggs or the vermiform developmental stages. The ability of these fungi to produce extracellular enzymes were also evaluated. This study highlights Indonesian nematode infected coffee rhizosphere soils as a rich source of nematophagous fungi, with eleven isolates showing promises to be used for integrated pest management strategies. Future work should assess field efficacy under local conditions while monitoring impacts on soil food webs and non-target organisms.